Proton Transfer: The First-Year Students’ Conceptual Understanding - Wisudawati, Asih Widi; Barke, Hans-Dieter (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2022)
Modern Chemistry education shows acid-base reactions by proton transfer with regard to Bronsted’s theory. Understanding how protons can be transferred by particles in solutions is quite challenging. The study aims to presents how university-first-year students are figuring out involved particles which take and give protons. Further, the enrolled participants in this study should explain how the process of proton transfer is running by selected particles but not by substances. Fifty-four students participated in this study that started from revealing participant’s experiences on their previous education at senior high school. Subsequently, researchers conducted a pretest, learning planning, and learning implementation, finally a posttest. Qualitative analysis is preferred to analyze students’ conceptions on particle level. The result shows us that there are two categories of participant’s difficulties. First is determining the involved particles either all particles or reacting particles. The difficulties dominate on mixing terminology of atoms, ions, and molecules, also on preferences of memorizing and calculating oxidation state for chemical equations. The subsequent difficulty is the proton transfer process that caused by participant’s failure on how they selected reacting particles. The systematic sequence on introducing and interpreting chemical equations has also presented as breakthrough.